Delivery of Genome Editing Reagents to Hematopoietic Stem/Progenitor Cells. (13th February 2018) - Hoban, Megan D.; Romero, Zulema; Cost, Gregory J.; Mendel, Matthew; Holmes, Michael; Kohn, Donald B.
Abstract: This unit describes the protocol for the delivery of reagents for targeted genome editing to CD34 + hematopoietic stem/progenitor cells (HSPCs). Specifically, this unit focuses on the process of thawing and pre‐stimulating CD34 + HSPCs, as well as the details of their electroporation with in vitro‐transcribed mRNA‐encoding site‐specific nucleases [in this case zinc‐finger nucleases (ZFNs)]. In addition, discussed is delivery of a gene editing donor template in the form of an oligonucleotide or integrase‐defective lentiviral vector (IDLV). Finally, an analysis of cell survival following treatment and downstream culture conditions are presented. While optimization steps might be needed for each specific application with respect to nuclease and donor template amount, adherence to this protocol will serve as an excellent starting point for this further work. © 2016 by John Wiley & Sons, Inc.